Wise use of coastal wetlands: 10-year reclamation vs. 3-year eco-governance in the Tiaozini Wetland, Jiangsu, China - Liang, Jiahui; Tian, Jiahui; Zuo, Ping; Dai, Ziyi; Jiang, Wenkui; Jin, Juan; Yan, Yuru (Frontiers in Marine Science, 2023)
Coastal wetlands provide extensive ecological services for life on Earth but are facing rapid global disappearance influenced by human activities and climate change. From 1984 to 2018, approximately 28% of the natural coastal wetlands in China were lost due to seawater intrusion, reduced sediment acquisition, urbanization, and reclamation. Tiaozini wetland used to be reclaimed during 2010-2019, and quickly shifted for conservation with less than 3 years. We analyzed 3 years of top-down eco-governance and bottom-up activities in Tiaozini, one of the typical wetlands with wise use instead of reclamation. Collaboration of stakeholders, such as the management company, local residents, tourists, scientific committees, NGOs, and media, facilitated the wise use of Tiaozini wetland as a successvie way towards eco-governance, including public participation and environmental education. Adaptive management, ecosystem-based management, and natural-based solutions play very important roles in eco-governance from both bottom-up and top-down approaches. Results showed that 3-year eco-governance induced great achievements in both biodiversity conservation and ecotourism development, which outweighs the 10-year reclamation for coastal wetlands exploitation.